Factors influencing survival and mortality among adult Aboriginal Australians with bronchiectasis—A 10-year retrospective study - Heraganahally, Subash S.; Gibbs, Claire; Ravichandran, Shiidheshwar J.; Erdenebayar, Davaadorj; Abeyaratne, Asanga; Howarth, Timothy (Frontiers in Medicine, 2024)
Background The prevalence of bronchiectasis among adult Aboriginal Australians is higher than that of non-Aboriginal Australians. However, despite evidence to suggest higher prevalence of bronchiectasis among Aboriginal people in Australia, there is sparce evidence in the literature assessing clinical parameters that may predict survival or mortality in this population. Methods Aboriginal Australians residing in the Top End Health Service region of the Northern Territory of Australia aged >18 years with chest computed tomography (CT) confirmed bronchiectasis between 2011 and 2020 were included. Demographics, body mass index (BMI), medical co-morbidities, lung function data, sputum microbiology, chest CT scan results, hospital admissions restricted to respiratory conditions and all-cause mortality were assessed. Results A total of 459 patients were included, of whom 146 were recorded deceased (median age at death 59 years). Among the deceased cohort, patients were older (median age 52 vs. 45 years, p = 0.023), had a higher prevalence of chronic obstructive pulmonary disease (91 vs. 79%, p = 0.126), lower lung function parameters (median percentage predicted forced expiratory volume in 1 s 29 vs. 40%, p = 0.149), a significantly greater proportion cultured non-Aspergillus fungi (65 vs. 46%, p = 0.007) and pseudomonas (46 vs. 28%, p = 0.007) on sputum microbiology and demonstrated bilateral involvement on radiology. In multivariate models advancing age, prior pseudomonas culture and Intensive care unit (ICU) visits were associated with increased odds of mortality. Higher BMI, better lung function on spirometry, prior positive sputum microbiology for Haemophilus and use of inhaled long-acting beta antagonist/muscarinic agents may have a favourable effect. Conclusion The results of this study may be of use to stratify high risk adult Aboriginal patients with bronchiectasis and to develop strategies to prevent future mortality.